A single mutation in the gatekeeper residue in TgMAPKL-1 restores the inhibitory effect of a bumped kinase inhibitor on the cell cycle. Issue 1 (April 2015) - Sugi, Tatsuki; Kawazu, Shin-ichiro; Horimoto, Taisuke; Kato, Kentaro
Graphical Abstract: Highlights: Substitution of Ser191 in TgMAPKL-1 changed T. gondii susceptibility to bumped kinase inhibitors. Inhibition of TgMAPKL-1 caused enlarged parasite cells in the host. Enlarged parasites replicated DNA but failed to complete cytokinesis. Inhibition of TgMAPKL-1 arrested the budding of daughter cells. Abstract: Toxoplasma gondii is the causative pathogen for Toxoplasmosis. Bumped kinase inhibitor 1NM-PP1 inhibits the growth of T. gondii by targeting TgCDPK1. However, we recently reported that resistance to 1NM-PP1 can be acquired via a mutation in T. gondii mitogen-activated protein kinase like 1 (TgMAPKL-1). Further characterization of how this TgMAPKL-1 mutation restores the inhibitory effect of 1NM-PP1 would shed further light on the function of TgMAPKL-1 in the parasite life cycle. Therefore, we made parasite clones with TgMAPKL-1 mutated at the gatekeeper residue Ser 191, which is critical for 1NM-PP1 susceptibility. Host cell lysis of RH/ku80 - /HA-TgMAPKL-1 S191A was completely inhibited at 250 nM 1NM-PP1, whereas that of RH/ku80 - /HA-TgMAPKL-1 S191Y was not. By comparing 1NM-PP1-sensitive (RH/ku80 - /HA-TgMAPKL-1 S191A ) and -resistant (RH/ku80 - /HA-TgMAPKL-1 S191Y ) clones, we observed that inhibition of TgMAPKL-1 blocked cell cycle progression after DNA duplication. Morphological analysis revealed that TgMAPKL-1 inhibition caused enlarged parasite cells with many daughter cell scaffolds and imcomplete cytokinesis. We conclude that the mutation in TgMAPKL-1 restored the cell cycle-arresting effect of 1NM-PP1 on T. gondii endodyogeny. Given that endodyogeny is the primary mechanism of cell division for both the tachyzoite and bradyzoite stages of this parasite, TgMAPKL-1 may be a promising target for drug development. Exploration of the signals that regulate TgMAPKL-1 will provide further insights into the unique mode of T. gondii cell division.